Jawapan

  • Pengguna Brainly
2016-03-17T15:15:49+08:00
Y = 12 - g 2y + 3g - 16 = 0 2(12-g) + 3g - 16 = 0 24 - 2g + 3g - 16 = 0 g = 16 - 24 g = - 8 y = 12 - (-8) y = 12 + 8 y = 20
1 5 1
2016-03-17T15:16:49+08:00
Starting with y+g=12 2y+3g=16 ... To solve for y: Multiply the first equation by -3 -3(y+g=12) Yielding -3y - 3g = -36 Add the the second equation 2y + -3y + 3g + -3g = 16 + -36 Combine like terms -y = -20 Divide both sides by -1 y = 20 ... To solve for x: Multiply the first equation by -2 -2(y+g=12) Yielding -2y - 2g = -24 Add the second equation -2y + 2y + -2g + 3g = -24 + 16 Combine like terms g = -8 ..Done..